2015
DOI: 10.1038/ncomms8304
|View full text |Cite
|
Sign up to set email alerts
|

The impact of DNA intercalators on DNA and DNA-processing enzymes elucidated through force-dependent binding kinetics

Abstract: DNA intercalators are widely used as fluorescent probes to visualize DNA and DNA transactions in vivo and in vitro. It is well known that they perturb DNA structure and stability, which can in turn influence DNA-processing by proteins. Here we elucidate this perturbation by combining single-dye fluorescence microscopy with force spectroscopy and measuring the kinetics of DNA intercalation by the mono- and bis-intercalating cyanine dyes SYTOX Orange, SYTOX Green, SYBR Gold, YO-PRO-1, YOYO-1 and POPO-3. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
211
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(240 citation statements)
references
References 51 publications
16
211
0
1
Order By: Relevance
“…Dye molecules induce structural changes in DNA [46], which disrupt the functions of DNA-binding proteins and enzymes [47]. A detailed understanding of how fluorescent dyes bind with host DNA may prove essential to drug development efforts [48], or DNA curtains studies [49].…”
Section: Resultsmentioning
confidence: 99%
“…Dye molecules induce structural changes in DNA [46], which disrupt the functions of DNA-binding proteins and enzymes [47]. A detailed understanding of how fluorescent dyes bind with host DNA may prove essential to drug development efforts [48], or DNA curtains studies [49].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have demonstrated the capability of optical tweezers techniques to measure the persistence length of the CIS-DNA complex and have shown that CIS binds cooperatively to the DNA molecule (19,20). In the same vein, using optical tweezers, still other authors have observed a reduction of DNA persistence length and DNA extension in the presence of intercalants (21)(22)(23), noting also that the measured values of the persistence length depend on the maximum stretching force (24). Finally, magnetic tweezers (MT) measurements have revealed the effect of drug binding on DNA nanomechanics by detecting persistence-length variations (15,25), or the presence of two different persistence lengths depending on the applied force (9), or the various effects of combining CIS and transplatin (26).…”
Section: Introductionmentioning
confidence: 92%
“…1(a)], thereby lengthening the DNA upon binding. 8,9 Both groove binders and intercalators have a well-defined orientation with respect to the helix axis of the DNA. For intercalators, the absorption and emission dipole moments are roughly perpendicular to the DNA helix axis.…”
Section: Introductionmentioning
confidence: 99%